Frames of venezuelan migration: an analysis of the information framing in the digital media El Tiempo (Colombia) and El Comercio (Ecuador): Luis Eduardo Ynciarte - Ynciarte, Luis Eduardo (Quórum Académico, 2021)
This research presents an analysis of the news generated by the main digital media El Tiempo (Colombia) and El Comercio (Ecuador) during 2019 regarding the migration of Venezuelans, under the argument that the media influence perception of their receivers. This study focuses on communication theories: (1) agenda setting, which explains how media selects and prioritizes daily news and (2) framing that points out how media approaches the information. A content analysis is established with 881 units taken from the sites eltiempo.com (435) and elcomercio. com (446). Finally, it is evident that (1) there is a marked trend in the coverage of information that is oriented to the use of official sources (2) the contents disseminated focus on reporting issues such as the migratory flow and cases of social conflict, crime or death where negatively frames Venezuelan migration.